Investigating Students’ Listening Skill Using Liveworksheet As An Outline Teaching Platform - Nurul Hidayah; Slamet Asari (UIR Press, 2022)
ABSTRACTThe COVID-19 pandemic has impacted education, so we need suitable media, especially for listening skills; one of the right platforms is liveworksheets. Liveworksheet provides many convenient features and a creative, innovative, and interactive platform in which there is an added interest for online learning to activities that show their listening skills ability. This study aimed to determine the students' listening skill ability and perspectives through liveworksheet platform. This study uses a quantitative method, and uses questionnaires also test survey instruments. The participants of this study were 52 students grade 2 at Ban KaengSriphum Junior High School, Loei, Thailand. The results showed that from the pre-test and post-test, liveworksheet can help student to their listening skill ability. Then, 50.9% of students strongly agree that listening lessons are essential, 43.4% strongly agree that the liveworksheet is an effective platform, 44.2% strongly agree that the platform needs to be maintained, 43.4 % strongly agree that liveworksheets are the expected media, and 39.6% of students strongly agree that liveworksheets are easy to reach media for listening skills. From these results, it can be said that liveworksheets platform can help students in listening skills ability.Keywords: Students Perspective, Liveworksheet, Listening Skill Ability